Transición energética en Colombia estrategias para la sostenibilidad energética colombiana (2024)
This study undertakes a detailed comparative study of the energy transitions of Colombia and Brazil and considers three fundamental objectives. The first phase will examine current regulations in both countries, from laws to ISO standards, to create a legal and strategic basis to guide the process towards sustainable energy sources. The study will move to a second phase, with a detailed analysis of Colombia's renewable energy projects, focusing on the production of hydroelectric, wind, solar, thermal and biomass energy. This analysis is complex and enriching by making important comparisons with the Brazilian reality and providing a more comprehensive and contextualized vision of the strategies implemented in both countries. The culmination of the work is in the third phase, when a specific PESTEL analysis of Colombia is carried out. This approach not only highlights the specific challenges Colombia faces in its energy sustainability efforts, but also provides a solid strategic map for informed decision making. Taken together, this study not only contributes to the theoretical understanding of the energy transition, but also provides practical and strategic guidance. Its reach extends beyond Colombia's borders and provides valuable perspective on the Latin American region. Ultimately, this initiative aims to accelerate the adoption of policies and strategies that promote a cleaner, more sustainable and more resilient energy future in the Colombian and Latin American energy landscape.